Praktik Developer Syariah Tanpa Kredit Perbankan Perspektif Fikih Muamalah (Studi Kasus di Perumahan Istiqomah Kabupaten Berau): Islamic Developer Practices Without Bank Credit from The Perspective of Fiqh Muamala (Case Study in Istiqoma Housing in Berau District) - Andi Dahmayanti; Munawara, Munawara; Risdayani, Risdayani; Rodhiyyah Nur Pratiwi (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
The research aims to analyse the law of sharia developer practices without bank credit in Istiqomah Housing in the perspective of fiqh muamalah. This research uses qualitative field research with a research approach using normative and sociological approaches. As for data collection through interviews and documentation, then the data is analysed using qualitative descriptive analysis. The results of the research found that long-term credit begins with negotiations between the housing authority and consumers regarding the fees to be paid, as well as determining the time to install the house with a maximum time of 10 years. This agreement is written, signed and owned by both parties. Home financing in Istiqomah housing uses an istiṣnā‘ contract, where istiṣnā’ is a form of sale and purchase contract that involves ordering the manufacture of goods. The housing developer provides a credit payment system without going through a bank, and this credit sale and purchase is allowed in sharia. The ruling on the sale and purchase of housing is permissible because it fulfils the pillars and conditions of the sale and purchase contract and does not contradict the Islamic Shariah. The implications of the research are expected to be a good reference for developers, consumers, and the community to always apply home sale and purchase financing in accordance with Islamic law.